Color in the Art-Productive Activity of Preschool Children - Litichenko, Olena; Masteruk, Darya (Educological discourse, 2023)
The article analyzes the theoretical aspects of the formation of ideas about colors in children from 1 to 7 years old. It was found that color is an important means of expressiveness in artistic activity, a way of organizing the aesthetics of life, self-expression. The issue of children's attitude to colors and their use in their own artistic and productive activities is highlighted. The study carried out a definitional analysis of the main concepts of the study: "color", "artistic and productive activity". The works of Ukrainian and foreign scientists dealing with the investigated problem are considered. The peculiarities of the use of color by children of older preschool age in artistic and productive activities were clarified, the influence of gender stereotypes on the perception and use of colors by children was confirmed. The influence of various motives on the artistic and productive activity of children and their relationship with the use of colors in creative activity are considered. It was found that children choose the color of materials for making products according to their own preferences, but the purpose of the product is a significant factor influencing their choice. Experimental research proves: children are ready to give in to their own desires and tastes are not based on their own preferences, but on the tastes of the recipient of the gift, so it allows us to note the influence of moral motives. The structure of artistic and productive activity of children of older preschool age is singled out. The conclusions of scientists regarding the perception of colors by older preschool children in modern practice have been confirmed.